Contractile activity attenuates autophagy suppression and reverses mitochondrial defects in skeletal muscle cells. Issue 11 (2nd November 2018) - Parousis, Alexa; Carter, Heather N.; Tran, Claudia; Erlich, Avigail T.; Mesbah Moosavi, Zahra S.; Pauly, Marion; Hood, David A.
ABSTRACT: Macroautophagy/autophagy is a survival mechanism that facilitates protein turnover in post-mitotic cells in a lysosomal-dependent process. Mitophagy is a selective form of autophagy, which arbitrates the selective recognition and targeting of aberrant mitochondria for degradation. Mitochondrial content in cells is the net balance of mitochondrial catabolism via mitophagy, and organelle biogenesis. Although the latter process has been well described, mitophagy in skeletal muscle is less understood, and it is currently unknown how these two opposing mechanisms converge during contractile activity. Here we show that chronic contractile activity (CCA) in muscle cells induced mitochondrial biogenesis and coordinately enhanced the expression of TFEB (transcription factor EB) and PPARGC1A/PGC-1α, master regulators of lysosome and mitochondrial biogenesis, respectively. CCA also enhanced the expression of PINK1 and the lysosomal protease CTSD (cathepsin D). Autophagy blockade with bafilomycin A1 (BafA) reduced mitochondrial state 3 and 4 respiration, increased ROS production and enhanced the accumulation of MAP1LC3B-II/LC3-II and SQSTM1/p62. CCA ameliorated this mitochondrial dysfunction during defective autophagy, increased PPARGC1A, normalized LC3-II levels and reversed mitochondrially-localized SQSTM1 toward control levels. NAC emulated the LC3-II reductions induced by contractile activity, signifying that a decrease in oxidative stress could represent a mechanism of autophagy normalization brought about by CCA. CCA enhances mitochondrial biogenesis and lysosomal activity, and normalizes autophagy flux during autophagy suppression, partly via ROS-dependent mechanisms. Thus, contractile activity represents a potential therapeutic intervention for diseases in which autophagy is inhibited, such as vacuolar myopathies in skeletal muscle, by establishing a healthy equilibrium of anabolic and catabolic pathways. Abbreviations: AMPK: AMP-activated protein kinase; BafA: bafilomycin A1 ; BNIP3L: BCL2/adenovirus E1B interacting protein 3-like; CCA: chronic contractile activity; COX4I1: cytochrome c oxidase subunit 4I1; DMEM: Dulbecco's modified Eagle's medium; GFP: green fluorescent protein; LSD: lysosomal storage diseases; MAP1LC3/LC3: microtubule-associated protein 1 light chain 3; MTORC1: mechanistic target of rapamycin kinase complex 1; NAC: N-acetylcysteine; PPARGC1A: peroxisome proliferative activated receptor, gamma, coactivator 1 alpha; PINK1: PTEN induced putative kinase 1; ROS: reactive oxygen species; SOD2: superoxide dismutase 2, mitochondrial; SQSTM1/p62: sequestosome 1; TFEB: transcription factor EB